Analysis the Influence of Digital Platforms On Increasing Interest In Alms Of Generation Z - Saputra, Septian Yudha; Musyafa', Muhammad Nadzir; Pamungkas, Bagas Aji; Sabrina, Erlina Putri Arya (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study examines the influence of digital platforms on Generation Z’s interest in almsgiving within the framework of Islamic values. Using a mixed methods approach with an explanatory sequential design, the research involved a survey of 60 respondents who had previously donated through digital means, followed by in-depth interviews with selected participants. The quantitative results reveal that perceived ease of use, accessibility, and trust in digital platforms significantly influence interest in digital almsgiving. Additionally, Islamic values such as religiosity, ibadah maliyah (financial worship), and the pursuit of barakah (divine blessing) play a central role in shaping intentions. Qualitative findings further show that emotional engagement, particularly empathy evoked by donation content and social encouragement from peers and influencers, enhances this interest. The study concludes that Generation Z’s participation in digital almsgiving is driven by a synergy of technological convenience, spiritual motivation, and emotional-social dynamics. These findings offer important implications for optimizing digital donation platforms and advancing Islamic digital almsgiving.